ASSESSMENT OF THE IMPACT OF PESTICIDES ON THE SOIL MICROBIAL COMMUNITY USING INTACT POLAR MEMBRANE LIPIDS AS BIOMARKERS - M. Suleman; B. J. Keely; S. Liaqat; W. Ali (Journal of Animal and Plant Sciences, 2020)
Intact polar membrane lipids (IPLs) have recently been used as biomarkers to assess the diversity in microbial community as a result of stress conditions. Present study was aimed to investigate the impact of pesticides and their transformation products (TPs) on the soil microbial community. Soil was treated with isoproturon (IPU), glyphosate (GLYP), thifesulfuron methyl, propyzamide and their TPs at their maximum application rates. After seven weeks, IPLs were extracted from the soil and analysed by HPLC ESI-MSn. The method was sensitive and effectively separated different classes of polar lipids on the basis of their head groups. The IPL profiles of IPU, GLYP and PROP treated soil showed significant (p<0.05) variations among the abundance of the polar lipids due to pesticide application. The impact of the pesticides was more obvious in changes induced in the relative amounts of phosphatidyl choline (PC), diacylglycerol trimethylhomoserine (DGTS), phosphatidyl ethanolamine (PE), monomethyl phosphotidyl ethanolamine (PMME), monogalactosyl diacylglycerol (GL) and phosphatidyl glycerol (PG). It was concluded that the botanical pesticides and their TPs can induce changes in soil microbial diversity. Moreover, IPLs can be used as biomarkers for the assessment of the microbial response toward environmental stressors.
Keywords: Intact polar membrane lipids (IPLs); soil microbial diversity; liquid chromatography-tandem mass spectrometry (LC-MS/MS); pesticides; transformation products; phospholipids; betaine lipids